A Longitudinal Reservoir Model of Stress Dissipation and the Influences of Concomitant Perceptions of Control. (16th December 2020) - Bergeman, C S; Joiner, Raquael; Nelson, Niccole; Deboeck, Pascal
Abstract: To characterize the stress regulation system, we use a reservoir to reflect how much stress an individual "holds" over time. Factors affecting what is contained in a stress reservoir are incoming stress (Input), accumulation/dissipation (Strdiss), and actions taken to discharge stress (e.g., Control). At the within person level, time-varying control predicts better Strdiss (β= -0.03±0.01, p <.001), even when controlling for between person differences (e.g., age, neuroticism) and between and within person impacts of Input. Thus, control reflects an important stress dissipation tool. Further analyses indicated a significant 2-way interaction between time-varying effects of Input and Control (β= 0.14±0.03, p <.0001) and Strdiss and Control (β= 0.60±0.18, p <.001) on self-reported health and a significant 3-way time-varying interaction of Input, Strdiss and Control on depression (β= -0.173±0.07, p <.012). Studies of this type move beyond the static assessments of risk and resilience to a more dynamic one.